Self - assembly technique for producing l-arginine / hydroxyapatite coatings on Ti6Al4V implants - Duru, Ilayda. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2017., 2017)
Inthepresentstudy, weintroduceaself-assemblymethodtoproduceL-arginine (L-Arg)/Hydroxyapatite (HA) coatings. Firstly, Ti6Al4V substrates were etched in a concentrated solution of HCl/H2SO4. ZrO2 was reactively sputtered on Ti6Al4V as an intermediate layer between HA and Ti6Al4V. Reactive magnetron sputtering was performed at 200 W and 200 ◦C for 4 hours. HA was deposited on ZrO2 layer by electrophoretic deposition (EPD) at 30 V in 205 seconds. HA suspension was obtained byultrasonicandmagneticagitationof1gHAin35mlisopropanolfor3hours. Finally, thesampleswereimmersedinL-Argsolutioninphosphatebuﬀeredsaline(pH=7.4)and incubated at room temperature for 24 hours. Scanning Electron Microscopy (SEM), XRay Diﬀractometry (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Raman and X-Ray Photoelectron Spectroscopy (XPS) analyses were performed to characterize the coated and uncoated Ti6Al4V implants. Raman and XRD spectra of ZrO2 layer demonstrated the characteristic peaks of monoclinic structure. The most characteristic bands on Raman spectrum were a doublet at 181 and 189 cm−1, a broad peak at 477 cm−1. Moreover, XRD spectrum revealed that ZrO2 coating had a monoclinic crystal structure. FTIR and C1s spectra spectra of L-Arg/HA coating revealed the formation of new bonds which were C-O/N and protonated O-C=O. According to XPS analyses, C/Ca ratio increased with the addition of L-Arg and Ca/P ratio was decreased. It can be concluded that L-Arg particles were self-assembled on HA layer by binding of the carboxyl group of L-Arg to calcium atoms of HA. Overall, L-Arg/HA coatings were successfully coated on ZrO2-coated Ti6Al4V orthopedic implants by self-assembly method.|Keywords : Self-assembly, amino acid, orthopedic implant.
Keywords: Self-assembly (Chemistry); Amino acid sequence.; Orthopedic implants.